TREM1—Microglia crosstalk: Neurocognitive disorders - Huashan Li; Wanqiu Yu; Xue Zheng; Zhaoqiong Zhu (Brain Research Bulletin)
Neurocognitive Disorders (NCDs) primarily affect cognitive functions, including learning, memory, perception, and problem-solving. They predominantly arise as pathological sequelae of central nervous system (CNS) disorders. Emerging evidence suggests that microglial inflammatory activation within the hippocampus underlies the pathogenesis of cognitive impairment. Triggering receptor expressed on myeloid cells 1 (TREM1), a pattern-recognition receptor on microglia, becomes upregulated in response to injury and synergistically amplifies inflammatory responses mediated by other pattern-recognition receptors, leading to uncontrolled inflammation. While TREM1 is lowly expressed in the resting state, its upregulation upon exposure to injurious inflammatory stimuli promotes microglial activation and contributes to the development of NCDs. Consequently, TREM1 may serve as a critical receptor in microglia-mediated inflammation. This article reviews the current understanding of TREM1 and its role in NCDs pathogenesis.